1994
DOI: 10.1007/bf00004357
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of insulin and liver glycogen contents in one- and two-year old Atlantic salmon (Salmo salar L.) during the period of parr-smolt transformation

Abstract: Plasma levels of insulin were measured by specific radioimmunoassay in 1-year and 2-year old Atlantic salmon (Salmo salar) parr during the period of parr-smolt transformation. The two-year old fish were of two different categories; silvering pre-smolts and previously mature male parr. If insulin plays an important role in parr-smolt transformation and/or subsequent osmoregulatory changes it was expected that the pre-smolts would show a different insulin profile compared to the mature male parr and one-year old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It has been previously suggested that low glycogen levels may be a major reason for the high death rate when smolts are transferred from fresh to salt water (Mayer et al 1994;. During the seawater challenge test in the present study, the glycogen levels in the smolts (C10 Wi group) were reduced, by 47% in the liver and 7% in the muscle.…”
Section: Smoltification and Osmoregulatory Abilitysupporting
confidence: 45%
See 1 more Smart Citation
“…It has been previously suggested that low glycogen levels may be a major reason for the high death rate when smolts are transferred from fresh to salt water (Mayer et al 1994;. During the seawater challenge test in the present study, the glycogen levels in the smolts (C10 Wi group) were reduced, by 47% in the liver and 7% in the muscle.…”
Section: Smoltification and Osmoregulatory Abilitysupporting
confidence: 45%
“…It has been previously suggested that low glycogen levels may be a major reason for the high death rate when smolts are transferred from fresh to salt water (Mayer et al . 1994; Plisetskaya et al .…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone (GH) has been shown to be photoperiod responsive (Bjornsson et al 1989(Bjornsson et al , 1995McCormick et al 1995), and increases in GH have been found as early as March in fish held under natural photoperiods. In addition, an increase in plasma insulin has been found in coho salmon Oncorhynchus kisutch as early as February (Plisetskaya et al 1988) and in Atlantic salmon smolts in March (Mayer et al 1994). Increases in either GH or insulin have been suggested to promote growth (Mommsen 1998).…”
Section: Energy Reserves Growth and The Winter-spring Transitionmentioning
confidence: 99%
“…As liver gets bigger in fish due to age, liver glycogen amount also increases (Shahidi and Dujanski, 1993). Mayer et al (1994) determined the highest liver glycogen values as 35 mg/g in 1 year old and 50 mg/g in 2 years old of Salmo salar. Heinimaa (2004) stated that liver glycogen values of Atlantic salmon consists 0.5 to 9.5% of the liver weight.…”
Section: Changes Depending On Agementioning
confidence: 95%